Subclinical Abnormalities of Visual Evoked Potentials and Blink Reflex in Patients with Fibromyalgia - Sidika Buyukvural Sen; Halil Can Alaydin; Halit Fidanci (Neurological Sciences and Neurophysiology)
Aims: Previous studies on event-related evoked potentials have suggested potential abnormalities in patients with fibromyalgia. This study aimed to investigate whether patients with fibromyalgia exhibited alterations in visual evoked potentials (VEPs) and blink reflex responses. Subjects and Methods: This prospective study included 40 female patients with fibromyalgia and 40 healthy female controls. Participants underwent pattern VEP (PVEP), flash VEP (FVEP), and blink reflex assessments. In addition, the Fibromyalgia Impact Questionnaire (FIQ) and the Visual Analog Scale (VAS) were administered to the fibromyalgia group. Results: The results obtained from PVEP, FVEP, and blink reflex studies showed no significant differences between the healthy control group and the patients with fibromyalgia. However, 5 (12.5%) patients with fibromyalgia had at least one VEP abnormality, and 7 (17.5%) exhibited blink reflex abnormalities. Moreover, a borderline positive correlation was found between the side-to-side ipsilateral R2 latency difference and FIQ scores (P = 0.049, r = 0.313) in patients with fibromyalgia. Conclusions: Although VEP and blink reflex responses did not significantly differ between patients with fibromyalgia and healthy controls, a subset of patients exhibited subclinical abnormalities. These findings suggest that subtle neurophysiologic changes may be present in fibromyalgia.